(untitled) (Ciudades, 2018)
"I received ’La Ville Radieuse’ - that dazzling Modern City proposal by Le Corbusier - I received it through Roberto Puig, my partner from the start of our studies. He had received it, apparently, through a nephew of Secundino Zuazo; that ought to have happened towards the end of the forties."